2013
DOI: 10.1111/jnc.12435
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive detection of neurochemical changes prior to overt pathology in a mouse model of spinocerebellar ataxia type 1

Abstract: Spinocerebellar ataxia type 1 (SCA1) is a hereditary, progressive and fatal movement disorder that primarily affects the cerebellum. Non-invasive imaging markers to detect early disease in SCA1 will facilitate testing and implementation of potential therapies. We have previously demonstrated the sensitivity of neurochemical levels measured by 1H magnetic resonance spectroscopy (MRS) to progressive neurodegeneration using a transgenic mouse model of SCA1. In order to investigate very early neurochemical changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 30 publications
5
23
1
Order By: Relevance
“…3). Unlike prior studies (Emir et al, 2013; Öz et al, 2010b; Öz et al, 2011b), taurine levels in the WT group were lower, rather than higher, than the condSCA1 [ 82Q ] mice. The reason for this difference is unclear, but may be related to a different osmolytic status of the tTA mice than the FVB strain, which we had used as the background control for the transgenic SCA1 model in the past (Öz et al, 2010b; Öz et al, 2011b).…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…3). Unlike prior studies (Emir et al, 2013; Öz et al, 2010b; Öz et al, 2011b), taurine levels in the WT group were lower, rather than higher, than the condSCA1 [ 82Q ] mice. The reason for this difference is unclear, but may be related to a different osmolytic status of the tTA mice than the FVB strain, which we had used as the background control for the transgenic SCA1 model in the past (Öz et al, 2010b; Öz et al, 2011b).…”
Section: Discussioncontrasting
confidence: 88%
“…Based on all our MRS studies in SCA1 mice so far, the earliest changes are observed in taurine, glutamine, tCr and tCho, indicative of osmolytic changes and of disturbances in membrane phospholipid and energy metabolism (Emir et al, 2013). These are followed by changes in the neuronal viability marker NAA, the putative gliosis marker Ins and later by the neurotransmitter glutamate (Öz et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduction in total NAA levels directly correlates with SCA1 patients' ataxia scores and similar changes have also been observed in SCA1 mouse models. Notably, these changes have been demonstrated to be dependent on the expression of mutant ATXN1 protein and its deletion in conditional SCA1 models rescues those deficits (Emir et al, 2013;Guerrini et al, 2004;Oz et al, 2010). Interestingly, N-acetylaspartate (NAA) is synthesized by mitochondria and is a neuron-specific metabolite.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, upon suppression of transgene expression in this model, both the cerebellar pathology and abnormal neurochemical levels returned towards normal [Oz, Vollmers, et al, 2011]. Finally, studies with a knock-in SCA1 model that displays milder cerebellar pathology than the transgenic line used in prior studies showed that neurochemical alterations can be detected prior to overt pathology in SCA1 [Emir et al, 2013]. To summarize, 1) 1 H MRS detects parallel neurochemical alterations in patients with SCA1 and SCA1 mouse models, 2) the same neurochemicals (NAA, myo -inositol, glutamate) reflect clinical status and pathological progression in SCA1, 3) neurochemical alterations are detectable prior to ataxia onset and overt pathology, and 4) reversal of neurochemical alterations with treatment is detectable by MRS.…”
Section: High Field Magnetic Resonance Spectroscopy In Movement Disormentioning
confidence: 99%